Schottky Diode Leakage Current Fluctuations: Electrostatically Induced Flexoelectricity in Silicon - Hurtado, C.; MacGregor, M.; Chen, K.; Ciampi, Simone (2024)
Nearly four decades have passed since IBM scientists pioneered atomic force microscopy (AFM) by merging the principles of a scanning tunneling microscope with the features of a stylus profilometer. Today, electrical AFM modes are an indispensable asset within the semiconductor and nanotechnology industries, enabling the characterization and manipulation of electrical properties at the nanoscale. However, electrical AFM measurements suffer from reproducibility issues caused, for example, by surface contaminations, Joule heating, and hard-to-minimize tip drift and tilt. Using as experimental system nanoscale Schottky diodes assembled on oxide-free silicon crystals of precisely defined surface chemistry, it is revealed that voltage-dependent adhesion forces lead to significant rotation of the AFM platinum tip. The electrostatics-driven tip rotation causes a strain gradient on the silicon surface, which induces a flexoelectric reverse bias term. This directional flexoelectric internal-bias term adds to the external (instrumental) bias, causing both an increased diode leakage as well as a shift of the diode knee voltage to larger forward biases. These findings will aid the design and characterization of silicon-based devices, especially those that are deliberately operated under large strain or shear, such as in emerging energy harvesting technologies including Schottky-based triboelectric nanogenerators (TENGs).